The valuation of hedge funds' equity positions - Gjergji Cici; Alexander Kempf; Alexander Pütz (University of Cologne, Centre for Financial Research (CFR), 2011)
We provide evidence on the valuation of equity positions by hedge fund advisors. Reported valuations deviate from standard valuations based on closing prices from CRSP for roughly seven percent of the positions. These deviations are economically significant for about 25 percent of the hedge fund advisors. Advisors with more pronounced valuation deviations show a stronger discontinuity in their reported returns around zero, manage a higher fraction of potentially fraudulent funds, show smoother reported returns, self-report to commercial databases, and are domiciled in offshore locations. Additional tests suggest that the documented equity valuation deviations respond to past performance.
Keywords: G23; G28; 330; hedge funds; fair value; return smoothing; valuation manipulation; fraud